Induction of Human Lung Mast Cell Apoptosis by Granule Permeabilization: A Novel Approach for Targeting Mast Cells - Paivandy, Aida; Sandelin, Martin; Igelström, Helena; Landelius, Per; Janson, Christer; Melo, Fabio R.; Pejler, Gunnar (Frontiers in Immunology, 2017)
Mast cells are implicated as detrimental players in inflammatory lung diseases, particularly asthma. Mast cells respond to activating stimuli by releasing a wide panel of pro-inflammatory compounds that can contribute profoundly to the pathology, and there is currently an unmet need for strategies that efficiently ameliorate harmful effects of mast cells under such conditions. Here we sought to evaluate a novel concept for targeting human lung mast cells, by assessing the possibility of selectively depleting the lung mast cells by induction of apoptosis. For this purpose we used lysosomotropic agents, i.e. compounds that are known to permeabilize the secretory granules of mast cells, thereby releasing the contents of the granules into the cytosol. Either intact human lung tissue, purified human lung mast cells or mixed populations of human lung cells were incubated with the lysosomotropic agents mefloquine or siramesine, followed by measurement of apoptosis, reactive oxygen species (ROS) production and release of cytokines. We show that human lung mast cells were highly susceptible to apoptosis induced by this strategy, whereas other cell populations of the lung were largely refractory. Moreover, we demonstrate that apoptosis induced by this mode is dependent on the production of ROS, and that the treatment of lung tissue with lysosomotropic agents causes a decrease in the release of pathogenic cytokines. We conclude that selective apoptosis of human lung mast cells can be accomplished by administration of lysosomotropic agents, thus introducing the possibility of using such drugs as novel therapeutics in the treatment of inflammatory lung disorders such as asthma.